SOCIAL STUDIES LEARNING ORIENTATION FOR THE FORMATION OF STUDENTS' SOCIAL ATTITUDES AT SMPN 1 TAROGONG KIDUL - Nurdin Miptahul Ulum; Tetep; Triani Widyanti (Institut Pendidikan Indonesia, 2022)
Forming social attitudes is one way to create a nation that has character. Problems that often arise in schools lately include the behavior of students who lack discipline, for example dressing not according to the rules, coming late to school, and being late for class. Then there is another problem of students who lack responsibility in carrying out assignments. This research aims to describe the magnitude of the influence of social studies learning on the social attitudes of students at SMPN 1 Tarogong Kidul. This research uses a quantitative, descriptive type approach in class VIII. The research population was 334 students who were then used as a sample of 34 respondents. The research results show that the relationship between social studies learning and social preparedness is in the sufficient category, namely 0.569, with an effect size of 32.4%. Research shows a positive and significant influence so that social studies learning must be more optimal so that students' social attitudes can be formed.